249 Effects of Heat Stress Mitigation Techniques on Feedlot Cattle Performance, Environmental, and Economical Outcomes in a Hot Climate. (7th December 2018) - Klopatek, S; Rivera, C; Gonzalez, A; Rotz, A; Mitloehner, F
Abstract: Heat stress in feedlot cattle is a major animal welfare and economic concern, costing the U.S. beef cattle industry up to 369 million annually. To mitigate the deleterious effects of heat stress on animal performance and feedyard productivity, a feedyard in central Mexico compared various cooling methods for finishing cattle. Using the Integrated Farm System Model (IFSM), a partial lifecycle assessment (LCA) was performed to determine economic returns and environmental footprints of various cooling methods. The two year feedyard study was arranged in a completely randomized design with four treatments and three replications/yr, with time as a block (n = 6). The four treatments included 1) conventional shade (control; SC; steel shade 1.8 m2 of shade/hd), 2) double conventional shade (DS; steel shade 3.6 m2 of shade/hd), 3) dome structures without fans (DSA; 8.5 m2/hd with 98% solar radiation blocked), and 4) domes with fans (DCA; three large sized low-speed fans). Each of the four treatments had 65 Bos indicus bulls, in a pen area of 570 m2. When compared to the control (DC), DCA improved final BW by 25 kg (P < 0.05), followed by DSA at 12 kg (P < 0.05), and DS at 5 kg (P> 0.05). When treatment results were extrapolated to the entire feedyard population (annual turnover of 209, 700 hd/yr), cattle in domed structures (DSA and DCA) versus steel shades (SC and DS) had reduced greenhouse gas (GHG) and ammonia (NH3) emissions on a kg of BW basis. Compared to the control (SC), DSA had the greatest economic return of 13.14/ hd, followed by DCA and DS treatments with a return profit of 7.47 and 7.03, respectively. Overall in this hot climate, the implementation of advanced shade structures improved cattle performance and profitability while reducing environmental impacts of beef production.